Effects of unaltered and bioconverted mulberry leaf extracts on cellular glucose uptake and antidiabetic action in animals - Sang-Hyuk Jung; Joo-Hui Han; Hyun-Soo Park; Do-Hyung Lee; Seok Jin Kim; Hyun So Cho; Jong Seong Kang; Chang-Seon Myung (BMC, 2019)
Abstract Background Mulberry is a Korean medicinal herb that shows effective prevention and treatment of obesity and diabetes. Bioconversion is the process of producing active ingredients from natural products using microorganisms or enzymes. Methods In this study, we prepared bioconverted mulberry leaf extract (BMLE) with Viscozyme L, which we tested in insulin-sensitive cells (i.e., skeletal muscle cells and adipocytes) and insulin-secreting pancreatic β-cells, as well as obese diabetic mice induced by co-administration of streptozotocin (100 mg/kg, IP) and nicotinamide (240 mg/kg, IP) and feeding high-fat diet, as compared to unaltered mulberry leaf extract (MLE). Results BMLE increased the glucose uptake in C2C12 myotubes and 3 T3-L1 adipocytes and increased glucose-stimulated insulin secretion in HIT-T15 pancreatic β-cells. The fasting blood glucose levels in diabetic mice treated with BMLE or MLE (300 and 600 mg/kg, PO, 7 weeks) were significantly lower than those of the vehicle-treated group. At the same concentration, BMLE-treated mice showed better glucose tolerance than MLE-treated mice. Moreover, the blood concentration of glycated hemoglobin (HbA1C) in mice treated with BMLE was lower than that in the MLE group at the same concentration. Plasma insulin levels in mice treated with BMLE or MLE tended to increase compared to the vehicle-treated group. Treatment with BMLE yielded significant improvements in insulin resistance and insulin sensitivity. Conclusion These results indicate that in the management of diabetic condition, BMLE is superior to unaltered MLE due to at least, in part, high concentrations of maker compounds (trans-caffeic acid and syringaldehyde) in BMLE.